The Effect of Health Education on the Level of Anxiety in Patients with Stroke - Hijrawaty Hijrawaty; Tommy Pangandaheng; Tri Nurminingsih Hatala; Hernita Frisnawati Purba; Ireine Tauran (GLOBAL HEALTH SCIENCE GROUP, 2021)
Anxiety faced by stroke sufferers is a serious problem. Health education can be used to overcome anxiety in stroke sufferers. Objective: to determine the effect of health education on the anxiety level of stroke patients at Laburan Baji Hospital, Makassar. The research design used was a pre-experimental study with the One Group Pre Post Experiment type. The population was stroke patients who were treated at Laburan Baji Makassar General Hospital, totaling 123 people. The sampling technique used purposive sampling and obtained 30 people. The instrument in this research is a questionnaire. The analysis showed that the majority experienced severe anxiety, namely 18 people (60.0%) during the pretest. posttest results showed a decrease in respondents with severe anxiety, namely 7 respondents (23.3%). Wilcoxon test with a value of p = 0.001 which means that there is an effect of providing health education on the anxiety level of stroke patients.